2017
DOI: 10.1155/2017/9454682
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Bullying in the Forestry Organization of Turkey

Abstract: It is observed that the importance of executive-employee relationships is continuously increasing in today's professional life in addition to the importance of leadership types of managers along with the efficiency of employees as well as the sufficiency of these people in their social relations. Communication of employees with one another and with their manager, along with their social relations, is among the most important factors that sustain an organization. Bullying is a kind of psychological terror that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The association between family structure and bullying also varied between studies. Four studies reported no association between workplace bullying and marital status [37,43,49,55]. On the other hand, three studies reported that single, separated, divorced, and widowed workers were more likely to suffer from bullying at work [34,46,56], while one study found a higher risk of bullying among married workers (odds ratio (OR) = 3.06 (1.41–12.94)) [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between family structure and bullying also varied between studies. Four studies reported no association between workplace bullying and marital status [37,43,49,55]. On the other hand, three studies reported that single, separated, divorced, and widowed workers were more likely to suffer from bullying at work [34,46,56], while one study found a higher risk of bullying among married workers (odds ratio (OR) = 3.06 (1.41–12.94)) [42].…”
Section: Resultsmentioning
confidence: 99%
“…However, data from the 5th European Working Conditions Survey suggested a strong association between lower educational level and bullying (OR = 5.51 (1.79–16.95)) [36]. At the same time, two Turkish studies with forest engineers reported a higher prevalence of bullying among those with a doctoral degree [37,55].…”
Section: Resultsmentioning
confidence: 99%
“…The results on the relationship between workplace bullying and educational qualifications are conflicting. A systematic review found that there was no association between educational level and workplace bullying [ 1 ], whereas there was a strong association between bullying and educational level in some studies [ 21 , 22 , 23 ]. These inconsistent results are not only limited to educational level but also extend to the marital status of employees.…”
Section: Introductionmentioning
confidence: 99%
“…Workers who were single regardless of whether they were separated, divorced, or widowed were more likely to be bullied in their workplace [ 24 , 25 , 26 ] but some studies reported a higher risk of bullying among married workers and those with children [ 21 , 27 , 28 ]. On the contrary, some studies found no association between workplace bullying and marital status [ 22 , 29 ]. The findings on occupation also yielded different results.…”
Section: Introductionmentioning
confidence: 99%
“…A6. Systematic Nature of NWB All 16 types describe NWB not as a one-time event but as a systematic, repeated, or persistent process (Loraleigh Keashly and Harvey, 2005;Bayramoglu and Toksoy, 2017;Baran Tatar and Yuksel, 2018). Since systematic NWB may lead to severe psychiatric and psychosomatic outcomes, the 6-month timeframe was originally chosen in a study by Leymann et al to observe the occurrence pattern for its relation to the assessment of various psychiatric disorders in NWB victims (Leymann and Tallgren, 1989;Leymann and Zapf, 1990;Leymann, 1996).…”
Section: A Occurrence Patterns Of Nwbmentioning
confidence: 99%